(3chcH GdQhVIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMeO Hf EHQGgje Hf eMeO GdYSGd GdYfGfi GdTGaYi s)
(3ChdgG (B:s
(3SHMGf Gddg aGJb GdG,gGQ hNGdb GdCRgGQ gPG eLehY MSf ai JGQjN LRjQI eUQ GdeSeGI HGdQhVI jTJed Ydi QhGFY GdCNHGQ s
(3BNQgG (B:s
(3hcGf GdHhUjQi TjNfG eNJUQ GdLQe heGJ ai GdeGQSJGf GdefUhQi ef GdbGgQI GfJgi edNUG ef GdeaJi dYdGeI Jbi GdOjf GdebQjRi s
(3HgG WeSs
(3Nefg CjVkG PcQ fgQ Gdfjd heG hQO ajg ef GdCNHGQ hGdCTYGQ haQZ ef JCdjag SfI (B895s
(3ai GdeYgO fSN CNQi HQbe (B1188 (3, (B1934 (3, (B1935 (3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs